THE MODEL OF LAW ENFORCEMENT FOR JUVENILE DELINQUENT IN THE PROCESS OF INVESTIGATION BASED ON LAW NUMBER 11 YEAR 2012 CONCERNING JUVENILE JUSTICE SYSTEM - Hamidah Abdurrachman; Fajar Ari Sadewo (Jurnal Dinamika Hukum, 2016)
ABSTRACTThis study analyses the application of law enforcement model on juvenille offender before the law. Especially, in investigations according to Act number 11, 2012 about Juvenille Penal Court system in Central Java. Since the act has been formally implemented, the penal court elements have been given two years time to prepare strategies in handling juvenille offender through Diversion with Restorative Justice approach. However, the implementation of Diversion needs several infrastructures such as Juvenille Investigators, Diversion Standard of Operation (SOP), and a proper place for investigating children and  mediation process, including children cells. This is an empirical study with primary and secondary sources, including analysis of Acts, literature review, and expert review. The data analysis will be done qualitatively.Keywords: Juvenille Offender, Restorative Justice, Law enforcement